Strategi Guru dalam Membelajarkan Siswa Membaca Permulaan di Kelas 2 SD Negeri 05 Pemuar - Waridah, Waridah; Anjelia, Resa; Sulistyo M, Nur (Medan Resource Center, 2023)
This study aimed to investigate teachers' strategies for teaching early reading and identify factors contributing to students' difficulties in the process. The research employed a qualitative approach, with the second-grade teacher at SD Negeri 05 Pemuar as the research subject. The focus was on understanding the teacher's methods for instructing students in early reading. Data collection involved interviews, observations, and document analysis, utilizing interview and observation sheets as research instruments. Data analysis encompassed data reduction, exposure, and drawing conclusions. Triangulation techniques were applied to ensure the validity of the research data. The findings revealed that teachers utilized various strategies, including the spelling, sound, syllabic, and global methods, to facilitate early reading skills. Factors influencing students' challenges in initial reading were linked to motivation, interest, social maturity, emotions, and adjustment, contributing to difficulties in letter recognition, syllabic reading, word decoding, and reading repetition.